ISLAM AND DISRUPTIVE TECHNOLOGIES - Shaikh Mohd Saifuddeen Shaikh Mohd Salleh (Khayra Ummah Series (No.7/9), 2023)
This volume is part of the Khayra Ummah series, being itself the culmination of a sequence of colloquium of several themes organized by IKIM. The issues addressed in this series are: Islamic economics; Islamophobia; governance; moral deterioration; disruptive technology; environmental degradation; and the Islamic mind.